Diabetes Impairs Cellular Cholesterol Efflux From ABCA1 to Small HDL Particles. Issue 9 (9th October 2020) - He, Yi; Ronsein, Graziella E.; Tang, Chongren; Jarvik, Gail P.; Davidson, W. Sean; Kothari, Vishal; Song, Hyun D.; Segrest, Jere P.; Bornfeldt, Karin E.; Heinecke, Jay W.
Abstract : Rationale: HDL (high-density lipoprotein) may be cardioprotective because it accepts cholesterol from macrophages via the cholesterol transport proteins ABCA1 (ATP-binding cassette transporter A1) and ABCG1 (ATP-binding cassette transporter G1). The ABCA1-specific cellular cholesterol efflux capacity (ABCA1 CEC) of HDL strongly and negatively associates with cardiovascular disease risk, but how diabetes mellitus impacts that step is unclear. Objective: To test the hypothesis that HDL's cholesterol efflux capacity is impaired in subjects with type 2 diabetes mellitus. Methods and Results: We performed a case-control study with 19 subjects with type 2 diabetes mellitus and 20 control subjects. Three sizes of HDL particles, small HDL, medium HDL, and large HDL, were isolated by high-resolution size exclusion chromatography from study subjects. Then we assessed the ABCA1 CEC of equimolar concentrations of particles. Small HDL accounted for almost all of ABCA1 CEC activity of HDL. ABCA1 CEC─but not ABCG1 CEC─of small HDL was lower in the subjects with type 2 diabetes mellitus than the control subjects. Isotope dilution tandem mass spectrometry demonstrated that the concentration of SERPINA1 (serpin family A member 1) in small HDL was also lower in subjects with diabetes mellitus. Enriching small HDL with SERPINA1 enhanced ABCA1 CEC. Structural analysis of SERPINA1 identified 3 amphipathic α-helices clustered in the N-terminal domain of the protein; biochemical analyses demonstrated that SERPINA1 binds phospholipid vesicles. Conclusions: The ABCA1 CEC of small HDL is selectively impaired in type 2 diabetes mellitus, likely because of lower levels of SERPINA1. SERPINA1 contains a cluster of amphipathic α-helices that enable apolipoproteins to bind phospholipid and promote ABCA1 activity. Thus, impaired ABCA1 activity of small HDL particles deficient in SERPINA1 could increase cardiovascular disease risk in subjects with diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.